Pengaruh Suhu dan Lama Perendaman dalam Air Dingin pada Praperebusan Terhadap Kualitas Bakso Ikan Patin (Pangasius pangasius) - Gerry Anggara; Rodiana Nopianti; Herpandi Herpandi (Universitas Sriwijaya, 2016)
This research studied about the effect of temperature and immersion time in cold water to the quality of catfish (Pangasius pangasius) meatball. This study used a factorial randomized block design models with two factors that were the temperature of water immersion (4 °C, 16 °C, 26 °C) and the immersion time (5, 15) minute. Each treatmens were repeated twice. Parameters observed were chemical analysis that includes moisture content, fat content, protein content and physical analysis that includes the gel strength, expressible moisture, microstructure and sensory analysis in the form of hedonic quality test. The results showed that the treatment temperature and immersion time significantly (p<0.05) affected the water content, gel strength, expressible moisture and sensory, while the levels of protein and fat were not significant. Based on microstructural observations using a SEM (Scanning Electron Microscope) show the structural differences between the samples treated and treated not. The best treatment is the treatment temperature of 4 °C and immersion time of 5 minutes.